Non-Alcoholic Fatty Liver Disease, Bile Acids and Intestinal Microbiota - R. V. Maslennikov; Yu. V. Evsyutina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim.  The aim of the review is to present current data on the relationship between non-alcoholic fatty liver disease (NAFLD) with the metabolic disorders of bile acids (BA) and changes in the composition of the intestinal microbiota.Background.  NAFLD is accompanied by a change in the intestinal microbiotic composition: the proportion of taxa deconjugating BAs increases, while the proportion of taxa converting primary BAs to secondary ones decreases. The number of bacteria forming lipopolysaccharide (LPS) also increases. LPS, entering the liver with the portal vein blood, promotes the development of its inflammation and insulin resistance. The disturbance of bile acid metabolism through the effect on the FXR and TGR5 receptors also leads to insulin resistance and liver steatosis. FXR probiotics and agonists are promising drugs for the NAFLD treatment.Conclusion.  In the course of NAFLD, a change in the composition of the intestinal microbiota is observed, which contributes to the development of inflammation in the liver and disrupts the metabolism of bile acids, leading to insulin resistance.